THE METHODOLOGY OF APPLYING NEW PEDAGOGICAL TECHNOLOGIES FOR THE FORMATION OF COMPETENCIES IN TEACHING THE SCIENCE OF ECONOMIC THEORY (Scientific journal of the Fergana State University, 2025)
In this article, the methodology of using modern pedagogical technologies for the formation of students' competencies in teaching the science of economic theory is highlighted. The purpose and objectives of the research, research methods, results and conclusions are presented in the article. Through such an approach, it is possible to create innovative solutions in teaching economics and develop students' knowledge, skills and competencies.